2021
DOI: 10.1111/famp.12713
|View full text |Cite
|
Sign up to set email alerts
|

Individual’s pretreatment psychological symptoms and progress in couples therapy: A person‐centered analysis

Abstract: This study examined how individual pretreatment symptoms (depression and anxiety) predicted longitudinal, relational processes in couples therapy (the therapeutic alliance and couple satisfaction). This study included 99 heterosexual couples receiving systemic couples therapy. Partners reported their individual pretreatment symptoms of depression and anxiety before intake. Each member reported their therapeutic alliance with the therapist at the end of sessions 2–8, as well as their couple satisfaction before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 71 publications
(114 reference statements)
1
7
0
Order By: Relevance
“…Furthermore, the focus of the study was on average weekly effects and it is possible that the bidirectional associations between alliance and depressive symptoms occur over longer periods of time during the treatment phase. For example, couples where both partners report higher depressive and anxious symptoms experience lower changes in alliance across the first eight sessions of treatment compared to couples where both partners report lower depressive and anxious symptoms (Wu et al, 2022). Another possible explanation is that both alliance and relationship satisfaction are inherently about interpersonal relationship dynamics, whether it be with a partner or therapist, whereas depressive symptoms are typically experienced as individual cognitive factors though they are also affected by other mechanisms (Wittenborn et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, the focus of the study was on average weekly effects and it is possible that the bidirectional associations between alliance and depressive symptoms occur over longer periods of time during the treatment phase. For example, couples where both partners report higher depressive and anxious symptoms experience lower changes in alliance across the first eight sessions of treatment compared to couples where both partners report lower depressive and anxious symptoms (Wu et al, 2022). Another possible explanation is that both alliance and relationship satisfaction are inherently about interpersonal relationship dynamics, whether it be with a partner or therapist, whereas depressive symptoms are typically experienced as individual cognitive factors though they are also affected by other mechanisms (Wittenborn et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, two recent studies found mixed associations between therapeutic alliance, depressive symptoms, and relationship satisfaction among partners in couple therapy (Wu et al, 2021(Wu et al, , 2022. Particularly, couples with higher depressive symptoms and anxiety among both partners had higher initial alliance in males and females, and declining rates of change across the first eight sessions of couple therapy for males but not females (Wu et al, 2022). Additionally, only higher alliance in females was associated with their own higher relationship satisfaction at session 4, but not depressive symptoms (Wu et al, 2021).…”
Section: Therapeutic Alliance and Sexmentioning
confidence: 99%
See 3 more Smart Citations